The density and diversity of endophytic bacteria and fungi of drought stress-resistant plant: Case study in Karanganyar District, Central Java, Indonesia - Sudadi; Rosariastuti MMA Retno; Hadiwiyono; Luthfi Irham (BIO Web of Conferences)
This study explored the density and diversity of bacteria and fungi in three soil types: Alfisol, Entisol and Vertisol in Karanganyar, Central Java, Indonesia. The aim of the study was to understand the effect of various soil types on endophytic populations. Samples were collected from drought-tolerant plants in each soil type and analysed by the Total Plate Count. The results showed significantly different at the density of bacteria, with Alfisol having the highest density, followed by Entisol and Vertisol. However, there was not significantly different in fungi. The microbial characterization showed several genera in each soil type. The result has revealed several genera of bacteria and fungi collected from drought-tolerant plants in each soil type. These results provide information about the distribution of endophytic bacteria and fungi in various soil types and their potential use as biofertilizer. The study highlights the need for further investigation of the factors that influence microbial distribution and the development of soil-specific management strategies to optimize microbial activity and increase plant productivity.